Pembuatan dan Pemasangan Plang Jalan sebagai Upaya Peningkatan Identitas Wilayah di Jorong Sapan Tanah Nagari Batu Bajanjang - Nuzul Hidayat; Geva Ufara; Daniel Arif Hendrawan; Tyara Deziska; Farid Rizqullah Putra; Mujadin Hafzil; Akbar Zikriratullah; Rezita Azizah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service program aimed to strengthen regional identity and improve public access to information through the making and installation of road signs in Jorong Sapan Tanah, Batu Bajanjang Village, Lembang Jaya District, Solok Regency. The main problem identified was the lack of optimal road signs, which made it difficult for visitors, guests, and newcomers to recognize certain locations. This activity used a descriptive qualitative approach through observation, coordination with the head of the hamlet and local community, and documentation. The implementation stages included location surveys, preparation of tools and materials, road sign design, painting, writing the names on the signs, installation, and final documentation. The result of this activity was the availability of road signs as visual information media that help people identify the area more easily. In addition, the road signs strengthened the identity of Jorong Sapan Tanah, improved the environmental appearance, and became a concrete contribution of KKN students to the community. This program is expected to be maintained properly so that its benefits can be felt sustainably.